IoT Service Based on BLE Technology - Bainak, Dmitrii (Savonia-ammattikorkeakoulu, 2018)
The purpose of this thesis was to create an IoT service capable of transmitting the temperature and the carbon dioxide measurements over BLE to a custom Android application. According to the plan, the Arduino platform, the BLE shield, the temperature and the gas sensor had to be combined as a single unit, which would measure the data and send it to the application. The app was aimed to display the measurements on the graphs and to exchange the data with the Savonia Measurements server. Moreover, it was planned to get familiar with the BLE protocol, the working priciples of the utilized sensors and some of the best practices of Android application development. Initially, the Arduino Uno board and Arduino programming were studied to comprehend the Arduino platform and its features. Next, the specifications and the basic concepts of the BLE protocol were explored to understand how the transmission of data via BLE occurs. Afterwards, a research about the BLE shield and its features was conducted in order to expand the capabilities of the Arduino Uno board by mounting the shield on top of the board. Then the sen-sors were studied and attached to the board. Subsequently, the board was programmed so that it could measure the temperature and the carbon dioxide through the sensors and exchange the measurements with the help of the BLE shield. Finally, the Android application was created according to some of the best practices of modern mobile soft-ware devolepment, providing the properly functioning graphs and a stable connection with the Savonia Measure-ment server. As a result of this thesis, a fully functioning IoT service based on BLE technology was implemented. Additionally, knowledge about the Arduino platform, the BLE shield, the aforementioned sensors, and the modern Android application development was acquired.